Experimental bovine trypanosomiasis. Changes in the catabolism of serum immunoglobulins and complement components in infected cattle. - Nielsen, K (1978)
The turnover of serum proteins of calves experimentally infected with Trypanosoma congolense was compared to that of normal uninfected cattle. All proteins examined had much increased catabolic rates in infected animals. In normal animals the average half-lives in days for each protein were: IgG1 17.4, IgG2 22.4, IgM 4.8, IgA 3.4, IgE 1.9, C1 5.6 and C3 2.9. In trypanosome infected cattle the average half-lives were IgG1 1.9, IgG2 1.7, IgM 0.9, IgA 1.2, IgE 0.9, C1 1.2 and C3 1.1 days.